Algorithmic Authority: Understanding the Construction of Digital Sanad in TikTok Dakwah. - Luthviyah Romziana; Zaimuddin; Ahmad Sahidah (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
The rapid growth of social media has transformed the landscape of Islamic dakwah, enabling platform algorithms to play an increasingly significant role in shaping religious authority. This study aims to examine how algorithmic authority influences the construction of digital sanad within the TikTok dakwah ecosystem and to explore its theoretical implications for contemporary Islamic authority and knowledge transmission. The study employed a qualitative literature review by synthesizing scholarly articles, academic books, conference proceedings, and research reports related to algorithmic authority, digital religion, Islamic epistemology, and social media communication. The findings indicate that digital sanad emerges through the interaction of platform algorithms, religious content creators, and audience engagement, creating a hybrid model of religious legitimacy that complements rather than replaces the classical concept of sanad. This study contributes by integrating perspectives from Algorithmic Authority Theory, Digital Religion, Networked Religion, Platform Governance, and Islamic Epistemology into a unified conceptual framework. The findings provide valuable insights for strengthening digital religious literacy and promoting responsible Islamic communication in the digital era.